Exploring the knowledge of community‐based nurses in supporting parents of preterm babies at home: A survey‐based study - Julia Petty; Lisa Whiting; Cathrine Fowler; Janet Green; Alison Mosenthal (Wiley, 2022)
Abstract Aim This study aimed to investigate the confidence levels, knowledge base and learning needs of community‐based nurses relating to the care of preterm babies and parents, to explore what education is required and in what format. Design An online survey methodology was used. Methods A 32‐item questionnaire was distributed via social media platforms to community‐based nurses in Australia. Results Descriptive analysis was undertaken relating to knowledge base, confidence levels, previous training, learning and resource needs and barriers to education. It was deemed vital to expand confidence and knowledge in this area. Gaps in learning resources were identified and a need for more training in topics such as developmental outcomes, feeding, expected milestones, weight gain, growth trajectories and supporting parents. Online resources were the preferred format to teach key knowledge to community‐based health professionals, tailored to the specific features of preterm babies and support needs of parents.